Persepsi dan Minat Mahasiswa Jurusan Akuntansi TerhadapMata Kuliah Akuntansi Syariah - Rika Amelia; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to find out how the perceptions and interests of students majoring in accounting towards sharia accounting courses. For this study using a qualitative method approach. The location of this research was conducted at the Faculty of Economics and Business of Karawang Singaperbangsa University. And for data collection using a questionnaire and distributed to 50 respondents. Testing this hypothesis using regression analysis. The result is that simultaneously student perceptions and student interests have a significant effect on sharia accounting courses. Partially, student perceptions and student interests have a positive effect on sharia accounting courses.